The effects of dietary Turkish propolis and vitamin C on performance, digestibility, egg production and egg quality in laying hens under different environmental temperatures - Seven, Pinar Tatli (Asian-Australasian Assoc Animal Production Soc, 2008)
In this study, the effects of propolis and vitamin C (L-ascorbic acid) supplementation in diets were investigated on feed intake (FI), body weight (BW), body weight gain (BWG), feed conversion rate (FCR) and digestibility and on egg production and qualities (weight, mortality, shell thickness) in laying hens exposed to heat stress. A total of 150 Hyline White Leghom, aged 42 weeks, hens was divided into five groups of 30 hens. Chicks were randomly divided into 1 positive control, 1 control and 3 treatment groups. The chicks were kept in cages in temperature-controlled rooms at 22 degrees C for 24 h/d (positive control, Thermoneutral, TN group) or 34 degrees C for 9 h/d from 08.00-17.00 h followed by 22 degrees C for 15 h (control, heat stress, HS group) and fed a basal diet or basal diet supplemented with vitamin C (250 mg/kg of L- ascorbic acid/kg of diet) or two levels of propolis (2 and 5 g of ethanol extracted propolis/kg of diet). Increased FI (p < 0.05) and improvement in FCR (p < 0.05), hen day egg (p < 0.05) and egg weight (p < 0.05) were found in Vitamin C and propolis-supplemented laying hens reared under heat stress conditions. Mortality rate was higher in the control group than TN, vitamin C and propolis groups (p < 0.05). Digestibility of dry matter, organic matter, crude protein and ether extract improved with increasing of both dietary vitamin C and propolis (p < 0.05). Vitamin C or propolis supplementation did not affect either the percentage shape index, yolk index or haugh unit and albumen index (p > 0.05). However, the egg shell thickness and egg shell weight appeared to be increased in Vitamin C and propolis groups in comparison to HS group birds (p < 0.05). In conclusion, dietary supplementation of laying hens with anti-oxidants (vitamin C and propolis) can attenuate heat stress-induced oxidative damage. These positive effects were evidenced by increased growth performance and digestibility, improvement of egg shell thickness and egg weight in comparison to non-supplemented birds. Moreover, supplementation with propolis (5 g/kg diet) was the most efficient treatment.
Keywords: vitamin C; propolis; heat; stres; laying hen